Efeito da utilização de ácido lático na qualidade de filés de peito de frango de corte - Marcos Tadeu Souza Aquino (2016)
The poultry meat is a healthy food of great biological value, with high content of protein, essential amino acids, vitamins and low fat, however, just like any other animal product, may suffer contamination during their technological process of obtaining and being contaminated with microorganisms associated with foodborne diseases. The use of organic acids such as lactic acid is carried out in some countries to ensure sanitizing protocol of chicken carcasses with the aim of reducing pathogenic and deteriorating microorganism count and getting a safe quality of the product.The objective of this study was evaluate the influence of use lactic acid, at concentrations of 5% and 7%, in the sensory quality of broiler breast fillets. The evaluation of sensory characteristics was carried subjective analysis (sensory analysis) evaluating the parameters color and odor of raw broiler breast fillets (multiple comparison test) and color, odor, flavor and texture in roast broiler breast fillets (multiple comparison test and ranking test); and objective analysis (instrumental) color (L*, a* e b*), shear force, thawing loss and cooking loss. The use of lactic acid caused sensory changes in raw broiler breast fillets in relation the odor and color and just changes the texture of roast broiler breast fillets. However, changing these characteristics did not influence, regardless of the concentration of lactic acid used, the preference of the evaluators in relation to the color, flavor and texture attributes, except for to the odor attribute, where the evaluators showed less preference for broiler breast fillets treated with lactic acid 7%. There was difference between the use of objective methods (equipment) and subjective (sensory panel) in the evaluation of the texture of roast broiler breasts after spraying of carcasses with lactic acid. While the sensory evaluation panelists were able to detect that the application of lactic acid changed the texture of the samples, it was not observed by evaluating the shear force. However, in relation to the color attribute, the evaluators in sensory analysis and the methodology used in the subjective evaluation were able to indicate the influence of lactic acid in the color of cut chicken breasts. The spraying of lactic acid in broiler slaughter shown to be an interesting technology, since this has caused a little sensory changes, especially at concentration of 5%, to inhibit the acquisition of broiler breast fillets by the consumer.